Calf circumference has a positive correlation with physical performance among community-dwelling middle-aged, older women - Wang, Po-Chun; Yeh, Wei-Chung; Tsai, Yi-Wen; Chen, Jau-Yuan (Frontiers in Public Health, 2022)
Sarcopenia and frailty are well-known public health problems in middle-aged and older populations. Calf circumference (CC) is a representative anthropometric index that may be useful for screening sarcopenia. Physical performance assessed by hand grip strength and gait speed, was used as a measure of sarcopenia and frailty. This community-based, cross-sectional study was conducted in Guishan District, Taoyuan City, between April and October 2017 to investigate the relationship between CC and physical performance among community-dwelling middle-aged and elderly populations in Taiwan and to evaluate potential differences in sex. CC tends to be an efficient predictor of physical performance in the setting of community health screening and outpatient clinics for community health examinations, where there is limited time for surveys. A total of 1308 volunteers aged 50-85 years were recruited. Volunteers who declined to participate and those with recent cardiovascular disease, inability to complete an interview, physical performance examinations, and body composition measurements were excluded from the study. A total of 828 participants were enrolled in this study (237 men and 591 women). The statistical methods applied in this study were the Mann-Whitney U test, independent two-sample t-test, chi-square test and multivariate logistic regression models. Significant differences were observed in age, waist circumference, appendicular skeletal mass index, calf circumference, hand grip strength, and income between men and women. No significant differences were observed between men and women in terms of body mass index, gait speed, exercise habits, or underlying disorders of diabetes mellitus, hypertension or hyperlipidemia. Comparing across three different CC tertiles, there were significant differences in age, body mass index, waist circumference, appendicular skeletal muscle index, gait speed and hand grip strength, in both men and women. On multivariate logistic regression, after adjusting for age, appendicular skeletal mass index, body mass index, exercise habits and income levels, CC was positively correlated with physical performance as measured by both gait speed (β=0.15, p=0.01) and hand grip strength (β=0.25, p<0.001) in women, compared to only hand grip strength (β=0.41, p<0.001) in men. Lower calf circumference is an independent risk factor for poor physical performance, especially among women.